Ontologia de ciclo de explora????o agr??cola - Melo, Di??genes Pacheco de (2017)
Improving the efficiency and the quality in agricultural production are fundamental needs of the producers. In an individual perspective, they need it for their own maintenance and pros-perity in a highly competitive market. Looking thru the society???s perspective, it is a condition for producing, with cleaner and more sustainable practices, adequate food and supplies in suf-ficient quantity to match the needs of a growing population. The technological evolution is a constant component that concerns the farmers. Several entities produce and disseminate key knowledge for this economy sector: which regions are suitable to the different cultures; what are the market variation prospects (of costs and revenues); what are the news about adminis-trative practices, crop driving techniques and technologies that enhance production. The influ-ence of these elements in the decisions made by the producers may represent improvements in productivity and in the quality of the products. This information is currently shared in formats and terms set individually by each institution, imposing difficulties for translation, causing inaccuracies and losses on the interpretation by those who use it. The present work aims to propose an ontology-based model, which uses the current information of these different or-ganizations. The built pattern shall use as input relevant formats which already exists and, through the knowledge of specialists, form a solution for better acquiring/transmitting the information about a given agricultural exploration cycle. The created model may be used as an easing up element for the transmission of information disposed by the agricultural produc-tion related entities, enhancing the interoperability and contributing to the knowledge trans-ference in this sector.